Tumor-targeted and nitric oxide-generated nanogels of keratin and hyaluronan for enhanced cancer therapy. Issue 25 (19th June 2018) - Sun, Zhe; Yi, Zeng; Cui, Xinxing; Chen, Xiangyu; Su, Wen; Ren, Xiaoxiang; Li, Xudong
Abstract : Tumor-targeted and nitric oxide-generated nanogels based on human hair keratin and hyaluronan for enhanced cancer therapy. Abstract : The development of safe and effective nano-drug delivery systems to deliver anticancer drugs to targeted cells and organs is crucial to enhance the therapeutic efficacy and overcome unwanted side effects of chemotherapy. Herein, we prepared CD44-targeted dual-stimuli responsive human hair keratin and hyaluronic acid nanogels (KHA-NGs) through a simple crosslinking method. KHA-NGs, which consisted of spheres 50 nm in diameter, were used as carriers to load the anticancer drug doxorubicin hydrochloride (DOX). The drug release, cellular uptake, cytotoxicity, and targeting ability of DOX-loaded KHA-NGs (DOX@KHA-NGs) were assessed in vitro and the anticancer effects were further evaluated in vivo . The DOX@KHA-NGs had a super-high drug loading capacity (54.1%, w/w) and were stable under physiological conditions (10 μM glutathione (GSH)), with the drug being rapidly released under a tumor cell microenvironment of trypsin and 10 mM GSH. Cellular uptake and in vitro cytotoxicity results indicated that DOX@KHA-NGs specifically targeted cancer cells and effectively inhibited their growth. Furthermore, KHA-NGs were capable of improving intracellular nitric oxide levels, which sensitizes the cells and enhances the anticancer efficacy of chemotherapeutic drugs. In vivo experiments showed that DOX@KHA-NGs had a better anti-tumor effect and lower side effects compared to free DOX. These results suggest that the bio-responsive KHA-NGs have potential applications for targeted cancer therapy.